Trends and Characteristics of Arabic Language Teaching Material Development by Pre-Service Teachers in Higher Education: A Systematic Literature Review - Abdul Basid; Fikry Firmansyah (Global Education Journal, 2026)
The development of Arabic teaching materials by prospective teachers in universities is an important issue in line with the increasing demands of 21st century competence and the integration of technology in education. However, a comprehensive study of the trends and characteristics of the development of Arabic teaching materials by prospective teachers is still limited. This research aims to synthesize trends, approaches, and challenges that arise in the development of Arabic teaching materials in the higher education environment. This study uses the Systematic Literature Review (SLR) method by following the PRISMA guidelines. Literature searches were conducted on Semantic Scholar, PubMed, OpenAlex, arXiv, and ClinicalTrials databases. Of the 123 documents identified, 37 studies met the inclusion criteria and were analyzed. Risk of bias was evaluated based on the relevant domain, while the level of certainty of the evidence was assessed using the GRADE framework. The results of the study show five main themes, namely: (1) the competence of prospective teachers in learning design, (2) the effectiveness of teaching materials and curriculum innovation, (3) the implementation of 21st century skills through the 4C framework, (4) the integration of technology and artificial intelligence in Arabic language learning, and (5) the quality of the teacher candidate education program. The dominant trends include the use of digital technology, the application of constructivistic approaches, and the strengthening of 21st century skills. However, various challenges are still found, such as curriculum incompatibility, limited digital resources, and lack of pedagogic training. This study shows that the development of Arabic teaching materials is moving towards a more digital, collaborative, and competency-based approach. However, the low to very low certainty of the evidence indicates the need for more rigorous experimental research to support the development of Arabic teacher education policies and practices.